Laparoscopic Cholecystectomy in a Patient With Situs Inversus Totalis Presenting With Cholelithiasis: A Case Report - He, Tao; Zou, Jieyu; Song, Haiyu; Yi, Bin; Sun, Ke; Yang, Juan; Lei, Tingting; Xu, Lin; Li, Guangkuo (Frontiers in Surgery, 2022)
Laparoscopic cholecystectomy is the standard treatment for cholelithiasis. A very rare condition named situs inversus should not be considered as a contraindication for laparoscopic cholecystectomy. Here, we reported a case of successful laparoscopic cholecystectomy in a patient with situs inversus totalis. We also described the technical advantages of this treatment and reviewed the literature.